"Stitch for Stitch, You Are Remembering": Knitting and Crochet as Material Memorialization. (20th October 2019) - Fisk, Anna
Abstract: This article explores the role of the crafts of knitting and crochet in memorialization, an aspect of how contemporary knitting culture uses craft as a means of connecting with the sacred. It argues that knitting and crochet as material memorialization is part of wider trends in late modernity: the sacralization of the family; the preoccupation with the past; and the seeking of connection with that which is perceived to have been lost. Drawing on qualitative interviews, it discusses participants' craft projects used to honor maternal heritage, uncover marginalized histories, make space for reflection in commemoration and grieving, maintain the presence of the dead, and provide tactile comfort in the face of loss.